2021
DOI: 10.1016/j.epsc.2021.101838
|View full text |Cite
|
Sign up to set email alerts
|

Multisystem inflammatory syndrome in children. An emerging clinical challenge for pediatric surgeons in the COVID 19 era

Abstract: Background/purpose Multisystem inflammatory syndrome in children (MIS-C) is a potentially life-threatening condition occurring 2–6 weeks after Coronavirus disease 2019 (COVID-19) in previously healthy children and adolescents, characterized by clinical and laboratory evidence of multiorgan inflammation. We reported the case of a 6-year-old child presented with acute abdomen and then diagnosed with MIS-C. In addition, to better portray this new entity, we performed a systematic review of MIS-C gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 61 publications
(55 reference statements)
3
33
1
1
Order By: Relevance
“…Between 95% and all of the patients with this entity have abdominal pain, vomiting or diarrhea [ 11 ]. Comparing gastrointestinal manifestations in adults with SARS CoV-2 infection, they are present in less than 15%, in children between 10 and 20% and in children or adolescents with a diagnosis of MIS-C, between 80 and 100% [ 2 , 8 , 17 ]. In the study by Miller et al, 84.1% had gastrointestinal symptoms (abdominal pain, vomiting and diarrhea), and 100% of the children under study had fever (N: 44), which is very similar to that described by Shema et al, in a description of 35 patients where 86% presented gastrointestinal involvement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Between 95% and all of the patients with this entity have abdominal pain, vomiting or diarrhea [ 11 ]. Comparing gastrointestinal manifestations in adults with SARS CoV-2 infection, they are present in less than 15%, in children between 10 and 20% and in children or adolescents with a diagnosis of MIS-C, between 80 and 100% [ 2 , 8 , 17 ]. In the study by Miller et al, 84.1% had gastrointestinal symptoms (abdominal pain, vomiting and diarrhea), and 100% of the children under study had fever (N: 44), which is very similar to that described by Shema et al, in a description of 35 patients where 86% presented gastrointestinal involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The SARS CoV-2 pandemic, declared by the World Health Organization (WHO) on March 11, 2020, since the beginning has had a differential behavior between children and adults, mainly due to the type of involvement, clinical manifestations and severity. Thus, in mid-May 2020, European researchers reported cases of patients with symptoms of severe inflammation and multisystemic involvement that was initially associated with a syndrome similar to Kawasaki disease [ [1] , [2] , [3] , [4] ]. From this description and the issue of the criteria both by the WHO and the Center for Disease Control and Prevention (CDC) a new differential diagnosis has been established in children with gastrointestinal symptoms and surgical abdomen [ 1 , 3 , [5] , [6] , [7] , [8] ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Valitutti et al based on their own experience, encourages the assessment of the activity of the heart muscle before the operation of exploring the abdominal cavity. A preliminary assessment of troponin, BNP, D-Dimer, ferritin and echocardiography can help to establish a precise differential diagnosis in children with acute abdomen, especially when in MIS-C evolution toward cardiogenic shock should not be neglected (14). Another recomendation is presented by Khesrani et al They advice that in atypical abdominal pain syndrome during this pandemic an abdominal CT angio-scan should be performer to look for vascular damages in order to establish an appropriate medical treatment (immunoglobulins, corticoids) (15).…”
Section: Discussionmentioning
confidence: 99%
“…44 Therefore, to prevent unnecessary surgical operations during the pandemic, it has been suggested that pediatric surgeons perform a myocardial evaluation and rule out the MIS-C in children who presented with acute abdomen. 45 Although any segment of the gastrointestinal tract can be compromised, there is a predominance of ileal and colonic inflammation among the patients. Progressive bowel obstruction which mainly recovers with medical treatment may occur.…”
Section: Clinical Featuresmentioning
confidence: 99%